On the genus Scaphisoma Leach, 1815 (Coleoptera: Staphylinidae: Scaphidiinae) from Georgia, with description of a new species - I. Löbl (Кавказский энтомологический бюллетень, 2022)
Five species of Scaphisoma Leach, 1815 are recorded from Georgia. The new species S. caucasicum sp. n. is described from Samegrelo-Zemo Svaneti region, and two, S. assimile assimile Erichson, 1845 and S. subalpinum subalpinum Reitter, 1880 are recorded for Georgia for the first time. The new species can be externally compared with North Korean S. hapiroense Löbl, 1968, from which it can be readily distinguished from in the antennomere V shorter than the combined length of the antennomeres III and IV, the very fine pronotal punctation, and the light apical area of the elytra weakly delimited. The aedeagal characters of S. caucasicum sp. n. are similar to those of Chinese S. latro Löbl, 2000.